KONSEP GHARĀR DAN PENGARUHNYA TERHADAP KEADILAN EKONOMI - Sarim Karimullah, Suud (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
This study explores how gharār can be identified and minimized in modern transactions that often involve high uncertainty. Library research is used in this study to collect, analyze and interpret data from various written sources in an integrative and comprehensive manner. The results state that the concept of gharār proves the flexibility and depth of Islamic law in responding to modern economic challenges, making it an ethical guide that avoids uncertainty and excessive speculation and promotes fairness, transparency and sustainability in transactions. More than just a prohibition, gharār is the foundation for formulating inclusive economic policies, addressing social inequality, poverty, and environmental degradation through an adaptive approach to technologies such as fintech and e-commerce without compromising sharia values. With collaboration between scholars, regulators, and practitioners, gharār serves as a universal principle that ensures the Islamic economic system remains globally relevant, not only as an alternative but also as a model of transformation towards a more just, sustainable, and collective welfare-oriented economy. Keywords: Gharār, Uncertainty, Justice, Islamic Economics.